The Role of Notaries in Making Sharia Banking Contract Deeds in Post-Constitutional Court Decisions Number 93/Puu-X/2012 - Alun Windari Praptonowati; Sulistyandari Sulistyandari; Rahadi Wasi Bintoro; Suyadi Suyadi (Authentica, 2021)
Notaries in the making of sharia contract acts are required to have an understanding of sharia contracts and laws. This study is to determine the application of the choice of forum in the settlement of Islamic banking disputes after the Constitutional Court decision Number 93 / PUU-X / 2012 concerning the Review of Law No. 21 of 2008 on Islamic Banking. As well as the role of the notary in making the Islamic banking deed and after the decision. The method used in this research is the normative legal method. There are three approaches used in this, as following: normative juridical research, namely the case, statutory and conceptual approach. The results of the research showed that after the issuance of Decision Number 93 / PUU-X / 2012, the settlement of Islamic banking disputes is an absolute authority within the Religious Courts (in litigation). This affirmation of the authority of the Religious Courts is supported by Perma Number 14 of 2016 concerning the Settlement of Sharia Economic Cases. The role of a notary in making sharia deeds must apply sharia principles in line with the Sharia Banking Law Number 21 of 2008 and it is important for a notary to have sharia certification so that its legality can be recognized. The role of the notary after the Constitutional Court Decision Number 93 / PUU-X / 2012 by stating that the settlement of sharia banking disputes is the absolute authority of the Religious Courts in making sharia deeds. In conclusion the Constitutional District Court is no longer authorized to resolve sharia economic disputes.Keywords: Sharia Contract, Choice of Forum, Role of Notary, Sharia Banking, Constitutional Court Decision Number 93 / PUU-X / 2012, Dispute